(untitled) (Academia Science Repository, 2023)
A number of scientific and research works are being carried out in the world to introduce children of preschool age to artistic works: development of oral speech skills in children through dialogic reading; development of interactive strategies for teaching pupils to learn the language of picture books; improvement of the didactic system of moral education of children by means of culturally authentic literature; formation of scientific concepts (science concepts) in children by using descriptive texts; formation of artistic perception and imagination of students through storytelling (storytelling - historical story). This article discusses the role of fiction in the development of children’s speech in preschool educational organizations and also gives recommendations on the development of children’s speech through the leading methods of introducing them to fiction.